A Study towards the Evaluation and Problems Related To Pow-er Quality - Praveen Kumar, M.; Dhanraj, K.; KBVSR Subrahmanyam, Dr. (International Journal of Engineering and Technology, 2018)
This examination paper gives fundamental thought regarding problems and evaluation related to power quality. We will center around issues, for example, harmonic distortion, short intrusion, long interference, low voltage, voltage sags, Unbalanced Loads, voltage swell, voltage spike, wiring and establishing, Energy wastage on abandoned space and poor power factor are specified for power quality.Â Â